Tumor mutational burden and driver mutations: Characterizing the genomic landscape of pediatric brain tumors. Issue 7 (9th May 2020) - Patel, Roshal R.; Ramkissoon, Shakti H.; Ross, Jeffrey; Weintraub, Lauren
Abstract: Background: Tumor mutational burden (TMB) and driver mutations are potential biomarkers to guide targeted therapy selection. Malignant gliomas with high TMB in children may preferentially benefit from treatment with immune checkpoint inhibitors (ICPIs). Higher TMB may relate to lower incidence of driver mutations, but this relationship has not been studied in pediatric brain tumors. Procedure: Comprehensive genomic profiling was performed on 723 pediatric (≤21 years) brain tumor samples using DNA extracted from formalin‐fixed paraffin‐embedded tissue. TMB was calculated as mutations per megabase and categorized as low (0‐6), intermediate (6‐20), or high (>20). Analysis included 80 clinically relevant driver mutations; genomic alterations known to confer a selective growth advantage. Results: Of 723 brain tumors, TMB was low in 91.8%, intermediate in 6.1%, and high in 2.1%. In the high TMB cohort, 93% of tumors harbored a driver mutation; 70% and 63% in the intermediate and low TMB cohorts, respectively ( P < 0.05). However, when excluding tumor suppressor genes, high TMB tumors had a decreased incidence of driver mutations ( P < 0.001). BRAF alterations were not identified in high TMB tumors, but were enriched in low TMB tumors ( P < 0.01). Conversely, there was an association between high TMB tumors and TP53 mutations ( P < 10 −13 ). Of the 15 tumors with high TMB, 14 were high‐grade gliomas and 13 had alterations in TP53 . Three homozygous mismatch repair deletions identified were associated with a higher TMB ( P < 0.01). Conclusions: Specific driver mutations appear to have a relationship with TMB. These represent populations in which ICPIs may be more or less effective.